Effect of nicotine- and tar-removed cigarette smoke extract on cancer metastasis - Yuta Takahashi; Takuya Araki; Ayumu Nagamine; Hideaki Yashima; Daisuke Nagano; Kyoko Obayashi; Koujirou Yamamoto (Universitas Padjadjaran (Unpad), 2021)
Cigarette smoking is known to impact the promotion of carcinogenesis and tumor metastasis. On the other hand, some components in smoke were found to have health-promoting effects, and cancer suppressor effects of components in tobacco smoke have attracted attention. Although some studies showed the cancer suppressive effect of cigarette smoke extract (CSE) in vitro study, the effect of CSE administration on cancer is controversial. In this study, we investigated the effect of CSE-administration on tumor metastasis in a spontaneous tumor metastasis model using B16-BL6 cells, which is more clinical conditions. C57BL/6NCr mice were subcutaneously inoculated B16-BL6 cells into the footpad of the right rear leg. CSE was intraperitoneally administrated for 28 days from the day of inoculation. At 2 weeks after inoculation, the primary focus was excised. Subsequently, survival days of the mice were recorded to determine the effect of CSE-administration on spontaneous metastasis. The effect of CSE, α, β-unsaturated ketones, and aldehydes on B16-BL6 cell invasiveness were confirmed by matrigel invasion assay. Survival days of mice injected with 100% CSE was significantly shortened than that of control. B16-BL6 cell invasiveness was accelerated by the treatment with 0.1% CSE and 3 μM of crotonaldehyde. Intraperitoneal CSE-administration may progress spontaneous metastasis of B16-BL6 cells via enhancement of B16-BL6 cell invasiveness. As the cause, we found that crotonaldehyde contained in CSE may enhance the invasion ability of cancer cells. To clarify the cancer-suppressing effect of tobacco components, the effect of crotonaldehyde-removed CSE on tumor should be assessed in detail. Keywords: cigarette smoke extract (CSE), metastasis, crotonaldehyde (CA), B16-BL6 mouse melanoma cells, invasion